Campuran Serbuk Batang Singkong dan Serbuk Daun Cengkeh untuk Pembuatan Obat Nyamuk Bakar - Sapto Kuncoro; Sandi Asmara; Warji Warji; Luthfi Wisnu Wijaya (Jurnal Agricultural Biosystem Engineering, 2022)
Cassava is a long-lived plant that grows in tropical areas and is very adaptable to the environment. The potential for cassava, especially in Indonesia, is dominated by Lampung Province with a harvest area of 342,100 ha. Lampung is also a province that distributes clove plants. One of the uses of cassava stem and clove leaf waste is making a powder to be used as a mosquito coil. The purpose of this study was to obtain the best quality from cassava stem powder, clove leaf powder, and white glue (PVAc) as an adhesive that conforms to the standards of the Indonesian Industry Standard (SII). The research method used was an experimental method using a completely randomized design (CRD) experiment. The test results for mosquito coils in accordance with the Indonesian Industrial Standard (SII) are the integrity test, and for tests that are close to the SII standard is the weight per unit, the test results. water content. For the long test burn with the longest result, which is 366.51minute and the density test with a result of 0.5323 g/cm³, and for test on  the effectiveness of mosquito coils who have a major influene on mosquitoes, namely P5 treatment, which showed that most of the mosquitoes stuck to the bottom and looked weak within ± 5 minutes of ignition. Key words: Cassava, Mosquito, Mosquito Coils.